Video‐mediated breaking bad news simulation. (7th June 2021) - Rivet, Emily Burke; Cholyway, Renee; Edwards, Cherie; Wishnoff, Matthew; Raza, Omar; Haynes, Susan; Feldman, Moshe
Abstract: Background: Communication between clinicians, patients, and families is a core component of medical care that requires deliberate practice and feedback to improve. In March 2020, the COVID‐19 pandemic caused a sudden transformation in communication practices because of new physical distancing requirements, necessitating physicians to communicate bad news via telephone and video‐mediated communication (VMC). This study investigated students' experience with a simulation‐based communications training for having difficult conversations using VMC. Methods: Thirty‐eight fourth‐year medical students preparing for their surgical residency participated in a simulated scenario where students discussed a new COVID‐19 diagnosis with a standardised family member (SFM) of a sick patient via VMC. Learners were introduced to an established communications model (SPIKES) by an educational video. After the simulation, SFM and course facilitators guided a debrief and provided feedback. Learners completed surveys evaluating reactions to the training, preparedness to deliver bad news, and attitudes about telehealth. Results: Twenty‐three students completed evaluation surveys (response rate=61%). Few students had prior formal training (17%) or experience communicating bad news using telehealth (13%). Most respondents rated the session beneficial (96%) and felt they could express empathy using the VMC format (83%). However, only 57% felt ready to deliver bad news independently after the training and 52% reported it was more difficult to communicate without physical presence. Comments highlighted the need for additional practice. Conclusion: This pilot study demonstrated the value and feasibility of teaching medical students to break bad news using VMC as well as demonstrating the need for additional training.